The Determinant Factors that Influence Repurchase Intention of Samsung Smartphone in Jabodetabek - Michael Rusiviro Jacob; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
Smartphone users has increase rapidly in Indonesia, many people start to use smartphone and one of the manufacturers of smartphone is Samsung. Samsung has been the leader of Smartphone in Indonesia for years, but recently it experienced a drop in worldwide sales and also in Indonesia. This study aims to find the determinants that influence Samsung Smartphones repurchase intention. This study uses 9 variables and uses SEM-PLS data analysis method. All respondents used in this research are 280 respondents that resides in Jabodetabek area and have used Samsung smartphone. The result show that brand preference, brand experience, and brand loyalty have a positive effect towards repurchase intention. Meanwhile, other variables such as self-congruity has no positive effect towards repurchase intention